P170 VALUE OF ELECTROCARDIOGRAPHIC SCREENING FOR EARLY DETECTION OF ARRHYTHMIC AND MALIGNANT HEART DISEASE IN CHILDREN. (18th May 2022) - Elhyka, A; Fumanelli, J; Di Salvo, G; Iliceto, S; Leoni, L
Abstract: Background: Twelve–lead electrocardiography (ECG) is a tool that can identify cardiac conduction abnormalities that predispose to sudden cardiac death (SCD) in completely asymptomatic subjects. The rate of sudden cardiac death in childhood is estimated at 1–1.5 cases per 100, 000 individuals and 10–15% of events occur during physical activity. We evaluated the importance of the electrocardiogram performed in childhood in the early diagnosis of asymptomatic electrocardiographic changes suggestive for electrical or structural heart disease potentially at risk of sudden death. Materials and Methods: we analyzed 623 patients aged 0–16 years who were referred to the pediatric arrhythmology clinic in Padua Hospital between October 2013 and March 2020. Patients were referred to our second–level clinic after a first electrocardiographic alteration found out in ECG screening performed for sports activity. All patients were evaluated with clinical history and ECG. Then, depending on the suspected pathology, Holter ECG, ergometric test, echocardiogram, MRI were performed for adequate risk stratification. Results: Of the 623 patients evaluated, 393 (63%) were referred by sports medicine, 179 (29%) by the hospital pediatric clinic or family pediatrician, and 51 patients (8%) were referred for familiarity. 45% of patients (280) were referred for suspected WPW; 124 patients (20%) for many BEV and suspected ARVD; 85 patients (14%) for suspected long QT, 31 patients (5%) for suspected Brugada pattern; 7 patients (1%) for suspected CPVT; 8 patients (1%) for electrocardiographic changes with suspected HCM; 1 patient (0.01%) for suspected short QT and 88 patients (14%) for other arrhythmic disorders not at risk of sudden death. The diagnosis of WPW was confirmed in 280 patients (100%), LQTS in 45 patients (52%), SQTS in 1 patient (100%), S. of Brugada in 8 patients (25%), CPVT in 5 patients (71%), HCM in 8 patients (100%) and ARVD in 6 patients (5%). Conclusions: Our study demonstrates that electrocardiographic screening in childhood allows early diagnosis and treatment of life–threatening arrhythmic heart disease.